(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2022)
The purpose of this article is to present the specifics of the possibility of solving problems occurring in business transactions through mediation alternative to court proceedings, which enables the parties to the dispute to settle the conflict faster and less costly, without the need to stop cooperation. To this end, the process of alternative dispute resolution through mediation will be discussed in detail, taking into account the entire mediation process. The rules of mediation will be presented, the benefits of using it in an ongoing dispute, as well as the course and costs of mediation proceedings. The mediator will be described in detail, with an indication of his competences necessary for effective mediation in commercial matters. The analysis of the number of cases referred to mediation by courts and out-of-court settlements referred for approval by mediators will be discussed. The data on the dissemination of mediation and the attitudes of lawyers to this institution will be analyzed.